MON-310 Factors Associated with Remission After Surgery for Acromegaly - Cunha, Clara (J Endocr Soc, 2020)
Background: Acromegaly is a disorder characterized by excessive growth hormone (GH) secretion, which, in most cases, is caused by a GH secreting adenoma. Surgical removal of the tumor via a transsphenoidal approach is the first choice treatment for most patients. The remission rate after an initial resection is 80 to 90 percent for microadenomas and less than 50 percent for macroadenomas. Objective: To analyze predictive factors of remission in acromegaly patients who underwent transsphenoidal surgery for GH secreting adenoma. Methods: From January 2006 to October 2019, 75 patients with GH secreting pituitary adenoma were evaluated at our center. Patients who had undergone medical treatment or radiotherapy as first treatment were excluded. A total of 60 patients were included in the analysis. Remission was defined as normal serum insulin-like growth factor-1 (IGF-1) age and sex adjusted and a random serum GH less than 1 ng/mL and/or nadir GH during oral glucose tolerance test <0.4 ng/mL. Results: We evaluated 60 patients (41 females and 19 males), with a mean age at diagnosis of 49.6 (ranged from 23 to 77 years). Mean initial IGF-1 was 905.3 ng/mL (range 100-324) and mean initial GH was 25.0 ng/mL (<2.5). Macroadenomas were more common than microadenomas (48 vs 12). The average maximum tumor diameter was 15.6 mm and 21 patients were graded as Knosp 3 or 4, which indicated cavernous sinus invasion. Patients were follow for 11.8 years. Overall, the remission rate was 50.0% after surgery. Mean age of patients in surgical remission (51.6 years) was higher than those patients not in remission (47.5 years) (p=0.439). Remission rates for microadenomas and macroadenomas were 75.0% and 44.9%, respectively (p=0.04). Patients who achieved remission had smaller tumors compared with those who failed to attain remission (mean diameter 11.6mm versus 17.8 mm). Using the Knosp classification system and preoperative magnetic resonance images to determine cavernous sinus invasion, Knosp grade 3 to 4 tumors were found in 5 patients in remission and in 16 patients with persistence of disease (p=0.003). Patients who achieved remission had a significantly lower preoperative IGF-1 level (650.5 ng/mL) compared with those who did not (1211.0 ng/mL) (p=0.04). Preoperative GH levels were lower for the patients who achieved remission (18.7 ng/mL) than for those who did not (32.5 ng/mL, p=0.006). Conclusions: In our study, predictors of biochemical remission after surgery were smaller tumor size, lower Knosp grade, and lower preoperative GH and IGF-1 levels.